2014
DOI: 10.1177/0022002713515401
|View full text |Cite
|
Sign up to set email alerts
|

The Geography of Ethnocentrism

Abstract: Hammond and Axelrod use an evolutionary agent-based model to explore the development of ethnocentrism. They argue that local interactions permit groups, relying on in-group favoritism, to overcome the Nash equilibrium of the prisoner’s dilemma and sustain in-group cooperation. This article shows that higher levels of cooperation evolve when groups are dropped from the model, breaking the link between ethnocentrism and cooperation. This article then generalizes Hammond and Axelrod’s model by parameterizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In Table , the six notions (preference, superiority, purity, exploitativeness, group cohesion, and devotion) represent first‐order expressions; intergroup and intragroup ethnocentrism fall under the category of second‐order dimensions, and group self‐centeredness and self‐importance, along with ingroup positivity and outgroup negativity are third‐order factors (Bizumic et al, ). While much of the early research in anthropology, psychology, and sociology primarily falls under the classical, often negative, view of ethnocentrism, recent research has embraced a far more nuanced and arguably more balanced view of the concept (see also Bausch, ).…”
Section: Treatment Of the Concept Of Ethnocentrism In Its Intellectuamentioning
confidence: 99%
“…In Table , the six notions (preference, superiority, purity, exploitativeness, group cohesion, and devotion) represent first‐order expressions; intergroup and intragroup ethnocentrism fall under the category of second‐order dimensions, and group self‐centeredness and self‐importance, along with ingroup positivity and outgroup negativity are third‐order factors (Bizumic et al, ). While much of the early research in anthropology, psychology, and sociology primarily falls under the classical, often negative, view of ethnocentrism, recent research has embraced a far more nuanced and arguably more balanced view of the concept (see also Bausch, ).…”
Section: Treatment Of the Concept Of Ethnocentrism In Its Intellectuamentioning
confidence: 99%
“…Hammond and Axelrod's results are sensitive to changes in the assumptions made about local interaction and reproduction [3,29]. The same is valid for this model.…”
Section: Robustness Checksmentioning
confidence: 73%
“…Reproduction is asexual and local, meaning that each agent can produce an offspring that shares its features (with a certain chance of mutation) and that the offspring is placed in an empty cell around its parent, if there is one. 3 The order in which agents are given the chance to reproduce is random. d) Each agent has a chance of dying equal to the death rate.…”
Section: General Setupmentioning
confidence: 99%
“…For example Pepper and Smuts [58] test the hypothesis that cooperation can emerge as a result of kin selection (the selection of behaviors which help genetically similar individuals at one's own expense) and the local clustering of trait groups. In other cases, such implicit effects were brought to light post hoc, as was the case of Bausch [9] who showed that the model of Hammond and Axelrod [37] is sensitive to the practice of placing offspring only in the neighborhoods of their parents. The insight was that the cooperation behavior did not emerge because of the tags as Hammond and Axelrod argued, but rather simply because agents interacted with their close kin most of the time.…”
Section: Selection and Survivalmentioning
confidence: 99%